Analisis Penerapan PSAK 45 (Revisi 2011) Terhadap Penyusunan Laporan Keuangan Entitas Nirlaba - Hastoni, Hastoni; Pamungkas, Bambang; Mustikawati, Dinah Sobar (Jurnal Ilmiah Akuntansi Kesatuan, 2015)
The financial statement is a very important information to commercial entities and non-profit entities. Due to the existence of the financial statements concemed people can find relevant infomation on the activities undertaken and the progress of the company or organization. Characteristics of non profit entities with different business entities, the main difference lies in the way the fimdamental entity obtaining the resources needed to perform various operations activities. The purpose of this study is to analyze the application of PSAK 45 (Revised 2011) in a non profit entity which shaped the foundation. The analysis was performed to obtain data and information relating to the above problem. In addition, to detennine the extent of compliance or confomity of the financial statements presented by the non profit entity of the provisions contained in Pemyataan Standar Akuntansi Keuangan (PSAK) Number of45 Research conducted by the author is in "Yayasan Dharma Setia Kosgoro" is located in Bogor. Yayasan Dharma Setia Kosgoro is one ofthe foundation which is a unit ofprivate education providers established on 9 September 1987. The results showed that Yayasan Dharma Setia Kosgoro has made the preparation of the financial statements fairly well. Foundations offinancial statements consist ofstatements offinancial position, statement of activities, statement of cash flows, and notes to the financial statements, it is in accordance with PSAK 45. Keywords : Nonprofit Entities, Financial Statement, PSAK 45